Management of Gastroesophageal Reflux Disease (GERD) - Dadang Makmun (The Indonesian Society for Digestive Endoscopy, 2001)
Even though there are still no epidemiological data on the prevalence of Gastro Esophageal Reflux Disease (GERD) in Indonesia, data from The Division of Gastroenterology Department of Internal Medicine Cipto Mangunkusumo Hospital demonstrate signs of esophagitis in 22.8% of all patients with dyspepsia who underwent endoscopic examination. Western countries report a higher rate of GERD than Asian and African countries, possibly due to dietary factors and increased obesity. Besides adequate history and physical examination, there are many other supporting examinations that could be performed to establish the diagnosis of GERD, especially endoscopy of the upper gastrointestinal tract and 24-hour esophageal pH monitoring. Even though this condition is rarely fatal, GERD patients should still receive adequate management. Most patients demonstrate a satisfactory response towards therapy, which includes life-style modification as well as medication. Currently, the drugs of choice for GERD are proton-pump inhibitors. A combination of proton-pump inhibitors and prokinetics produces a better effect. Patients resistant to medical treatment or those with recurrent esophageal stricture should be considered for anti-reflux surgery. Keywords: gastroesophageal reflux, diagnosis, prokinetics, proton-pump inhibitor.